Do anti-dumping rules facilitate the abuse of market dominance? - Martin Theuringer; Pia Weiss (Universität zu Köln, Institut für Wirtschaftspolitik (iwp), 2001)
We discuss the effects of AD-protection in a standard Dixit model of entry deterrence. In an AD-regime, the newcomer is constrained by a minimum-price rule in addition to existing irreversible entrance costs. For minimum prices which lie below the Stackelberg one, we find that AD-rules distort competition. We show that AD-protection increases the advantages of entry deterrence for a wide range of combinations of sunk costs and minimum prices. When entrance costs are high, consumer welfare is lower in an AD- regime than under free trade. Consequently, AD-protection facilitates the abuse of market dominance.
Keywords: F14; L40; 330; Anti-dumping; abuse of market dominance; strategic firm behaviour; Antidumping; Markteintritt; Marktmacht; Wettbewerbsbeschränkung; Theorie